دور القيادات التربية في تطبيق أدارة الجودة الشاملة بمر حلة الأساسي في سلطنة عمان - Salem Said Saif Al-Mantheri
This study aimed to identify the role of educational leaders in the implementation of total quality management in basic education in the Sultanate of Oman, This study also aimed to identify the availability of basic requirements and reach a workable model proposed for the application of Total Quality Management.The researcher has used the documentary approach for the preparation of the theoretical framework and descriptive analytical approach, data were obtained from a sample using the Statistical . Package for Social Sciences processing program (SPSS).The study has showed a high level of awareness and understanding of the educational leaders to the importance of applying total quality management, but also has showed a lack of some of the total quality management requirements, such as support of senior management, dissemination of total quality culture and continuous training. The study recommended the need for a clear declared vision and a strategic plan for implementation of total quality management, and the need to hold seminars, conferences and workshops to disseminate the philosophy and principles of total quality management, and the importance of holding training courses for all educational leaders to unify the implementation of total quality management procedures in basic education schools.